Postfeminism™: celebrity feminism, branding and the performance of activist capital. Issue 7 (3rd October 2021) - Chidgey, Red
ABSTRACT: This article contributes to postfeminist media debates by interrogating an emerging configuration of celebrity feminism; one in which authenticity, entrepreneurial subjectivities and intersectionality mark the uneasy contours of a new political subject. Coining the term "activist capital", this paper moves beyond the impasse of celebrity feminism debates (where branding and commerce = bad, grassroots organising = good) to establish the uneven conditions through which celebrity feminist activisms are accepted, even deferred to, in media and activist accounts. Drawing on an illustrative case study of the high-profile Amber Rose SlutWalk (2015–2018), a Los Angeles-based monetised and branded edition of an existing political movement against sexual violence, this paper employs a discourse analytical approach to argue that celebrity and activist cultures condition each other. Aided by digital media, a celebrity activism nexus is now emergent that is mediated by practices of individualised consumer capitalism and oriented by explicit social justice frameworks, troubling dominant narratives of depoliticised postfeminist sensibilities. These ambivalences, where commodification no longer holds the power of disavowal it once did, and where grassroots activism and celebrity culture collide, condition the emergence of new activist arrangements in this late capitalist moment.